Weight trajectories and disordered eating behaviours in 11‐ to 12‐year‐olds: A longitudinal study within the Danish National Birth Cohort. (23rd April 2019) - Stemann Larsen, Pernille; Nybo Andersen, Anne‐Marie; Olsen, Else Marie; Kragh Andersen, Per; Micali, Nadia; Strandberg‐Larsen, Katrine
Abstract: Objective: To examine how childhood weight trajectories are associated with disordered eating behaviours (DEBs) in early adolescence. Methods: Self‐reports on DEBs (fasting, purging, and binge eating) were obtained from 18, 337 children in the 11‐year follow‐up of the Danish National Birth Cohort. For this population, birth register information on gestational age and birth weight was categorized into the following: small, appropriate, and large for gestational age. Prospective parent‐reported height and weight data at child ages 1 and 7 years were dichotomized using standardized cut‐offs into non‐overweight and overweight. A 12‐category weight trajectory variable was created, and the associations between weight trajectory and DEBs were estimated using logistic regression. Results: In total, 7.0% 11‐ to 12‐year olds reported DEBs. Compared with children born appropriate for gestational age and being non‐overweight at age 1 and 7 years, children born small for gestational age and who were overweight at age 1 and 7 years had a very high risk of disordered eating (OR 7.00; CI [2.57, 19.40]). The statistical analyses revealed, however, that overweight at age 7 years was the main contributor and independently of trajectory increased the risk of disordered eating at age 11–12 years significantly (OR 3.16 CI [2.73, 3.65]). Conclusion: Overweight not in the first year of life, but at age 7 years was more predictive for DEBs.